Regulation of eukaryotic mRNA deadenylation and degradation by the Ccr4-Not complex - Pavanello, Lorenzo; Hall, Michael; Winkler, Gerlof Sebastiaan (Frontiers in Cell and Developmental Biology, 2023)
Accurate and precise regulation of gene expression programmes in eukaryotes involves the coordinated control of transcription, mRNA stability and translation. In recent years, significant progress has been made about the role of sequence elements in the 3’ untranslated region for the regulation of mRNA degradation, and a model has emerged in which recruitment of the Ccr4-Not complex is the critical step in the regulation of mRNA decay. Recruitment of the Ccr4-Not complex to a target mRNA results in deadenylation mediated by the Caf1 and Ccr4 catalytic subunits of the complex. Following deadenylation, the 5’ cap structure is removed, and the mRNA subjected to 5’-3’ degradation. Here, the role of the human Ccr4-Not complex in cytoplasmic deadenylation of mRNA is reviewed, with a particular focus on mechanisms of its recruitment to mRNA by sequence motifs in the 3’ UTR, codon usage, as well as general mechanisms involving the poly(A) tail.